Manajemen Bandwidth Menggunakan Router Mikrotik dan Radio Ubiquity UBNT Litebeam M5 300 - Roberto Kaban; Tri Indah Prasasti; Asprina Br. Surbakti (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2022)
Wireless computer network is a very modern technology in the world of computer networks, this technology connects computers without using cables but using waves with a frequency of 2.4 GHz. In a wireless network, the user or users connect to the internet using air media through an access point device. This wireless-based network makes it easier for people to access the internet wherever they are. The design of this network installation consists of installing an RJ-45 connector on a UTP cable, radio configuration, Access Point, Mikrotik RB750 server configuration, and bandwidth management configuration. The existence of a wireless network at the Suka Damai Village Office, Hinai District, will make it easier for employees and the public to access the internet practically. In addition, configuring a wireless network is not so difficult, as long as it follows the rules for creating a network.